Actigraphic Recording of Manic Symptoms Induced by Methylphenidate - Tuuli Lahti; Sami Leppämäki; Pekka Tani; Timo Partonen (Case Reports in Medicine)
Objective. Attention-deficit hyperactivity disorder (ADHD) is a developmental disorder characterized by a long-standing pattern of impulsive behavior, hyperkinesia, and inattention. Psychostimulants, for example, methylphenidate, are the treatment of choice for ADHD both in children, adolescents, and adults. Method. The effect of methylphenidate on sleep structure is not well known. We studied the effect of long-acting methylphenidate on sleep in adult ADHD patients, in a naturalistic treatment setting, using actigraphic and polysomnographic recordings. Results. One of our patients experienced manic episode after starting methylphenidate. A wrist-worn accelerometer recording demonstrated a decrease in the duration and quality of sleep. After discontinuation of methylphenidate treatment, the patient's symptoms subsided and there was no need for hospital admission. Actigraphic recording showed a decrease in the amount and quality of the patient's sleep as triggering factor for the manic symptoms. Conclusions. Disruptions of the sleep-wake cycle are probably important etiologic factors in mood disorders, especially bipolar disorder. The changes in length and quality of sleep described in this case report bear close resemblance to those of patients with a manic episode, although these symptoms were induced by methylphenidate.